2019
DOI: 10.2139/ssrn.3446774
|View full text |Cite
|
Sign up to set email alerts
|

Firm Heterogeneity and Trade in EU Countries: A Cross-Country Analysis

Abstract: Firms are heterogeneous, even within narrowly defined sectors. This article surveys the relevant theoretical and empirical literature on firm heterogeneity and external trade. By innovatively exploiting rich crosscountry micro-aggregated data sourced from the ECB Competitiveness Research Network (CompNet), this study investigates the main implications of firm heterogeneity for trade by EU countries, presenting a set of stylized facts. On the one hand, exporting firms are larger, more productive and pay higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Following the self-selection mechanism proposed by [30], the empirical literature has found that other characteristics, in addition to productivity, such as size, capital, technological intensity, skilled-labour intensity, are also important to understand the decision of firms to become involved or not in foreign markets [18][19][20][21][22].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…Following the self-selection mechanism proposed by [30], the empirical literature has found that other characteristics, in addition to productivity, such as size, capital, technological intensity, skilled-labour intensity, are also important to understand the decision of firms to become involved or not in foreign markets [18][19][20][21][22].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…There is widespread empirical evidence on the existence of the self-selection mechanism at country level, for instance [29] for US firms; [43] for Taiwanese and Korean firms; [38] for Colombian, Mexican and Moroccan; [44,45] for Vietnamese; [46] for Eastern European and Central Asian countries; [17,47] for China; [21,42] for Italian; [19,34] for India; [48] for the European Union, South America and China. [32] for Chile; [20] for Indonesia; [2] for the UK; [22] for 14 EU countries; [31] for Sweden.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations